ØªØ·ÙˆÙŠØ± Ù…Ù‚Ø±Ø± Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙØµÙ„ Ø§Ù„Ø¹Ø§Ø´Ø± Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ù…Ø¹Ù„Ù…Ø§Øª Ù†Ù‡Ø¶Ø© Ø§Ù„ÙˆØ·Ù† Ø§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© - Nur Syahida Urwati; Ruwaida Hudatullah; Suaidi Suaidi (Lughatu Ad-Dhat, 2023)
Speaking proficiency is one type of language ability to be achieved in modern language teaching, including Arabic. Speaking is the main means of fostering mutual understanding, reciprocal communication, using language as the medium. In other words, speaking ability does not only play a role in language learning but also plays an important role in other learning. Based on the results of interviews with Arabic teachers at MA Mu'allimat NWDI Pancor, researchers found that there was little willingness and motivation of students to learn Arabic, minimal provision of vocabulary to practice speaking Arabic and the absence of the Maharah Kalam module to facilitate Arabic practice. The learning media used is an Arabic lesson package book. So it is necessary to develop the Maharah Kalam module to make it easier to speak Arabic. The aims of this study were: 1) To develop the speaking skill module for class X MA Mu'allimat NWDI Pancor, 2) To find out the response of material experts, media/design experts and students to the speaking skill module for class X MA Mu'allimat NWDI Pancor, 3) To find out the students' speaking ability in Arabic from the development of the speaking skill module for class X MA Mu'allimat NWDI Pancor. The research method used in this study refers to the R&D model with the ADDIE model which is one of the systematic (structured) learning design models, which means that it is programmed in sequence as an effort to solve student problems related to the required learning resources and student characteristics. The research that produces the final product in the form of a Maharah Kalam module is a type of R&D (Research and Development) using the ADDIE development model. The ADDIE model development flow is in stages (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The results of the material expert validation for the material in the speaking skill learning module were 88% (feasible). And the validation results of design/media experts for the speaking skill module design are 92% (Very Feasible). The response of students after learning to use the speaking skill module was 92% of the response